Analisis Penerapan Sistem Akuntansi Dalam Pembukuan Kas PKK Di Dusun Sumur Pandan - Jessica Aranda Windartik; Abu Darim (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The Research aims to analyze the application of the accounting system in PKK cash bookkeeping in Sumur Pandan Hamlet, Bandungsekaran Village, Balongpanggang District, Gresik Regency. The data studied was in the form of the application of the accounting system in PKK cash bookkeeping. data collection techniques used interviews and documentation. The data analysis technique used is a case study. The results of this study indicate that PKK cash bookkeeping in Sumur Pandan Hamlet, Balongpanggang District, Gresik Regency has not implemented cash bookkeeping in accordance with the accounting system. Because the cash bookkeeping that is made is only year-end bookkeeping. This can make it difficult for some parties if they need financial information at any time for decision making.